2015
DOI: 10.1108/h-07-2014-0051
|View full text |Cite
|
Sign up to set email alerts
|

Financial inclusion of the poor: from microcredit to Islamic microfinancial services

Abstract: Purpose – The purpose of this paper is to initiate a direct discourse towards an Islamic microfinance focus agenda for the economic enlistment of the poor minority community and to allow poorer households in the financial inclusion. The issue of the Indian conventional microfinance institutions in failing to attract the poorest of the poor amongst Muslims is important for the purpose of this paper. This study explores a Shari’ah-compliant microfinance system which will create a level of playing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 9 publications
(12 reference statements)
0
35
0
5
Order By: Relevance
“…An ideal society in Islam is where rules that relate to fair and just earning of income, such as the prohibition of interest, limiting profit earnings in favour of equitable distribution, holding workers in very high esteem and opposing the exploitation of labour are found (Mirakhor and iqbal, 2014). The study conducted by Hassan (2015) and Atia (2010) showed that Islamic financial instruments can play significant roles in enhancing financial inclusion. Naceur, Barajas and Massara (2015) argued that institutionalization of Islamic redistributive mechanisms such as Zakat, Sadaqah, Qardhul Hassan might assist in enhancing financial inclusion.…”
Section: Financial Inclusion In Nigeriamentioning
confidence: 99%
“…An ideal society in Islam is where rules that relate to fair and just earning of income, such as the prohibition of interest, limiting profit earnings in favour of equitable distribution, holding workers in very high esteem and opposing the exploitation of labour are found (Mirakhor and iqbal, 2014). The study conducted by Hassan (2015) and Atia (2010) showed that Islamic financial instruments can play significant roles in enhancing financial inclusion. Naceur, Barajas and Massara (2015) argued that institutionalization of Islamic redistributive mechanisms such as Zakat, Sadaqah, Qardhul Hassan might assist in enhancing financial inclusion.…”
Section: Financial Inclusion In Nigeriamentioning
confidence: 99%
“…Likewise, according to Wulandari and Kassim (2016), IMFIs provides financial services not only for the poor but also for the poorest in the informal sector of the economy, which are usually being funded using external sources such as Zakat, Infaq and Shadaqah. Furthermore, another study finds that there are some opportunities capable of improving the economic conditions of the poor Muslim communities through IMFIs, based on the Islamic principle (Hassan et al, 2015).…”
Section: Financial Inclusion and Alleviation Of Poverty Issuesmentioning
confidence: 99%
“…Abul Hasan (Hasan, 2015) dalam penelitiannya menyatakan bahwa pembiayaan mikro syariah sebetulnya bisa menyasar kepada kelompok yang selama ini tidak terakses oleh lembaga keuangan konvensional. Adanya akses terhadap pembiayaan mikro syariah bisa menghindarkan kemiskinan bagi para keluarga yang miskin.…”
Section: Literasi Dan Inklusi Keuangan Syariahunclassified